Recurrent hypokalemia and hypotension with unspecified cause in pregnancy: a warning sign of rare antenatal Barrter syndrome - Rika Bur; Meutia Gebrina; Muhammad Alifian Remifta Putra; Rachmat Dediat Kapnosa; Muhammad Maulana Wildani; Didi Danukusumo; Febby Elvanesa Sandra Dewi (Arterial Hypertension)
BACKGROUND: Hypokalemia is a frequent clinical disorder characterized by potassium levels under 3.5 mmol/L. In some cases, the cause can be challenging to be identified, resulting in suboptimal therapy. Thus, a comprehensive evaluation of the possible cause needs to be performed. CASE PRESENTATION: We report a 29-year-old woman who was 24 weeks pregnant and had a major complaint of weakness all over her body. In the last 4 years, the patient had a history of repeated hospitalizations due to hypokalemia. There was no history of diarrhea, taking routine medication, and thyroid disease. Fetal movements are recorded to be active, and there are no signs and symptoms of abdominal contractions. It was reported the same complaint was experienced by one of the patient’s children. A history of recurrent hypokalemia in the patient’s parents was denied. Physical examination shows that hemodynamic parameters are within normal limits, except blood pressure, which tends to be low, ranging between 80/60 and 100/70. Motoric strength was found to be weak in all four extremities. Laboratory examination revealed hypokalemia, high transtubular potassium gradient (TTKG) combined with respiratory alkalosis and metabolic alkalosis. Even though potassium correction management was carried out both intravenously and orally, the potassium level in the blood persistently fell after treatment. CONCLUSION: Recurrent hypokalemia and hypotension in these patients suggest rare causes with suspicion towards Bartter syndrome. This disorder cannot be cured and requires lifelong potassium substitution therapy. Early detection and appropriate management are essential as this syndrome is associated with higher antenatal and neonatal mortality.